Návrh nosné železobetonové konstrukce administrativního objektu - Blažek, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Obsahem diplomové práce je návrh základové desky a železobetonových stěn podzemní části administrativního objektu s ohledem na mezní stav šířky trhlin. Je řešeno provedení styků jednotlivých částí konstrukce proti pronikání podzemní vody do interiéru. Je provedena výkresová dokumentace navržených části. V teoretické části jsou zaznamenány zásady návrhu a provádění bílých van.

The subject of this thesis is the project of the foundational board and of reinforced concrete walls of the underground office building with respect to the limit state of crack width. There is designed the execution of joints of various parts of the construction against infiltration of groundwater into the interior. The drawing documentation of designed parts is performed there. In the theoretical part, there are logged the design principles and implementation of the white tubs.
Design of reinforced concrete structure of administration building
Keywords: beton; ocel; železobeton; zatížení; zemní tlak; podzemní voda; tlak vodního sloupce; mezní stav; únosnost; šířka trhlin; vynucená namáhání; pracovní spáry; těsnění spár; concrete; steel; reinforced concrete; load; earth pressure; ground water; the pressure of the water column; limit status; strength; crack width; forced strain; construction joints; seal joints